High Glucose Activates Prolyl Hydroxylases and Disrupts HIF-α Signaling via the P53/TIGAR Pathway in Cardiomyocyte - Jian-Xiong Chen; Lanfang Li; Aubrey C. Cantrell; Quinesha A. Williams; Heng Zeng (Cells, 2023)
The induction of hypoxia tolerance has emerged as a novel therapeutic strategy for the treatment of ischemic diseases. The disruption of hypoxic signaling by hyperglycemia has been shown to contribute to diabetic cardiomyopathy. In this study, we explored the potential molecular mechanisms by which high glucose (HG) impairs hypoxia-inducible factor-α (HIF-α) signaling in cardiomyocytes. The exposure of H9c2 cell lines to HG resulted in time- and concentration-dependent decreases in HIF-1α and HIF-2α expression together with an increase in prolyl hydroxylase-1,2 (PHD1 and PHD2) expression, the main regulators of HIF-α destabilization in the heart. The exposure of H9c2 cells to normal glucose (5.5 mM) and high glucose (15, 30, and 45 mM) led to dose-dependent increases in p53 and TIGAR and a decrease in SIRT3 expression. The pretreatment of H9c2 with p53 siRNA to knockdown p53 attenuated PHD1 and PHD2 expression, thus significantly enhancing HIF-1α and HIF-2α expression in H9c2 cells under HG conditions. Interestingly, pretreatment with p53 siRNA altered H9c2 cell metabolism by reducing oxygen consumption rate and increasing glycolysis. Similarly, pretreatment with TIGAR siRNA blunted HG-induced PHD1 and PHD2 expression. This was accompanied by an increase in HIF-1α and HIF-2α expression with a reduction in oxygen consumption rate in H9c2 cells. Furthermore, pretreatment with adenovirus-SIRT3 (Ad-SIRT3) significantly reduced the HG-induced expression of p53 and PHDs and increased HIF-1α levels in H9c2 cells. Ad-SIRT3 treatment also regulated PHDs-HIF-1α levels in the hearts of diabetic db/db mice. Our study revealed a novel role of the HG-induced disruption of PHDs-HIF-α signaling via upregulating p53 and TIGAR expression. Therefore, the p53/TIGAR signaling pathway may be a novel target for diabetic cardiomyopathy.